2013
DOI: 10.5897/ajb2013.12308
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of some important phytochemical, nutritional properties and toxicological potentials of ethanol extracts of Newbouldia laevis leaf and stem

Abstract: The pytochemicals, nutritional and toxicological potentials of the ethanol extracts of the leaf and stem of Newbouldia laevis was investigated in this study. The percentage yields of N. laevis ethanol leaf and stem extracts were found to be 7.44 and 3.30% (w/w), respectively. The preliminary phytochemical screening showed that ethanol leaf and stem extracts contains alkaloids, flavonoids and tannins. The quantitative phytochemical analysis showed that the leaf and stem extracts contained respectively: alkaloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
4
10
0
Order By: Relevance
“…The higher efficacy of root powder and extract of N. laevis may be ascribed to some toxic phytochemical compounds in roots that may not be present in stem of this plant. N. laevis root bark had been reported to contain alkaloids, tannins, flavonoids, saponins, cyanogenetic glycosides, cardiac glycosides and phenylpropanoids (Germann et al, 2006;Akerele et al, 2011) while the stem barks contained tannins, flavonoids, and alkaloids (Anaduaka et al, 2013). Most of these compounds had been reported for their considerable toxicity and antifeedant effect towards insects (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The higher efficacy of root powder and extract of N. laevis may be ascribed to some toxic phytochemical compounds in roots that may not be present in stem of this plant. N. laevis root bark had been reported to contain alkaloids, tannins, flavonoids, saponins, cyanogenetic glycosides, cardiac glycosides and phenylpropanoids (Germann et al, 2006;Akerele et al, 2011) while the stem barks contained tannins, flavonoids, and alkaloids (Anaduaka et al, 2013). Most of these compounds had been reported for their considerable toxicity and antifeedant effect towards insects (Yang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The screening also shows the presence of flavonoids in all the plants' extracts except C. adansonii root. The presence of variety of phytochemicals in the present study gives the indication that the plants, extracts could be used for curative activity against pathogens and therefore could explain their use traditionally for the treatment of wide array of illness including malaria (Anaduaka et al, 2013). Similarly, a number of researchers have linked the presence of certain phytochemicals as responsible for the treatment of specific diseases.…”
Section: Resultsmentioning
confidence: 96%
“…Sha'a et al (2014) reported that mice fed with up to 3000 mg/kg body weight of the ethanolic extract of Anacardium occidentale (cashew) showed sign of weakness but later became active and the authors concluded that the plant extract is safe. In some other toxicological studies, results revealed that dosage up to 5000 mg/kg body weight of ethanolic extracts of Newbouldia laevis (Anaduaka et al, 2013), aqueous leaf and root extracts of Cymbopogon citrates (Arome et al, 2016) and crude hydroalcoholic extracts of Embelia schimperi (Debebe et al, 2015) are safe. There are other studies that revealed toxicity of the extracts of plants at a lower dose than the findings of this work.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the anti-diabetic activity of the leaf extract has been reported by Owolabi et al, (2011) and Anaduaka et al, (2013a). Literature have also reported the phytochemicals constituents present in Newbouldia laevis (Akaneme,2008;Ogbe et al, 2009;Anaduaka et al, 2013b). Additionally, some of these plants are known to possess anti-fertility effect through their action on the hypothalomopituitory-gonodal axis or direct hormonal effects on reproductive organs.…”
Section: Introductionmentioning
confidence: 99%